(untitled) (SciELO Preprints, 2025)
The overlooked narrative about the origin of quantum nature in atoms primarily stems from a close examination of two sequential events from the past. The first event was Einstein’s attribution of quantum characteristics to light waves in his effort to elucidate the photoelectric effect, which ascribed both a corpuscular and wave nature to light. The second event involved de Broglie’s proposal regarding the wave nature of material particles, such as electrons, suggesting that they too possessed both corpuscular and wave characteristics. This advancement led to the emergence of a new branch of mechanics, termed quantum mechanics, which posits that the energy associated with any particle cannot be continuously altered but can assume a specific or some finite value, thereby endowing energy with a quantum form. This quantum nature of matter was perceived to arise from its dual wave-particle nature. It was later revealed that this mechanics exhibits a probabilistic character, which has sparked considerable debate among physicists. Essentially, the prevailing question at that time revolved around how electrons are stabilized within atoms and how these atoms can emit light waves of specific frequencies. In addressing this question, physicists, despite their limited resources, conducted high-quality experiments during the initial three decades of the 20th century, yielding significant conclusions. However, they occasionally overlooked critical signals obtained from these experiments. Had they not done so, the current understanding of physics might have been markedly different. This paper seeks to reassess those signals that were intermittently disregarded and constructs a comprehensive narrative regarding the potential impact they could have had on the evolving mechanics of that era, as well as the alternative perspective of physics that might have emerged from them.